REPRODUCTIVE PERFORMANCE OF BALI CATTLE IN KARANGASEM DISTRICT - E., Nafisah; Sumardani, N. L. G.; Dewantari, M. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aimed to determine the reproductive performance of Balinese cattle in Karangasem Regency. This study was a survey research of Balinese cattle breeders with purposive sampling method, and each sub-district was taken as much as 10% of the total population in each sub-district in Karangasem Regency, totaling 36 breeders. Data were analyzed by descriptive analysis, while to see the reproductive performance of Balinese cows from two mating systems, Two Independent Sample T-test was used. The results showed that the reproductive performance of Balinese cows in Karangasem Regency, Bali Province was quite good in terms of variables. The results of data analysis both on the variables of S/C, calving interval, age of first lambing, and empty period with aspects of artificial insemination and natural mating showed results that were not significantly different or nonsignificant in each sub-district. Based on the results of the study, it can be concluded that the reproductive performance of Balinese cows in Abang, Kubu, and Sidemen Districts of Karangasem Regency, Bali Province has good potential and there is no difference in the average reproductive performance of Balinese cows.  Reproductive performance in the form of age at first calving, service per conception (S/C), calving interval, and day open is good enough and in the normal category.